2021
DOI: 10.1016/j.waojou.2021.100517
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccine-associated anaphylaxis: A statement of the World Allergy Organization Anaphylaxis Committee

Abstract: Vaccines against COVID-19 (and its emerging variants) are an essential global intervention to control the current pandemic situation. Vaccines often cause adverse events; however, the vast majority of adverse events following immunization (AEFI) are a consequence of the vaccine stimulating a protective immune response, and not allergic in etiology. Anaphylaxis as an AEFI is uncommon, occurring at a rate of less than 1 per million doses for most vaccines. However, within the first days of initiating mass vaccin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
219
0
11

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(234 citation statements)
references
References 22 publications
4
219
0
11
Order By: Relevance
“…The results of our study indicate that neither in the patients with a history of allergy/anaphylaxis nor in the non-allergic group, administration of the first dose effected sensitization to the vaccine components that would result in a higher rate of hypersensitivity reactions after the second dose. It needs to be emphasized, however, that the study patients with a history of allergy and/or anaphylaxis who demonstrated good vaccine tolerance constituted a group of individuals who had been qualified for vaccination following guidelines and recommendations prerequiring stratification and phenotyping of such patients [22,23]. Patients with a history of anaphylaxis to vaccines and injection drugs containing polyethylene glycol (PEG), as potentially susceptible to hypersensitivity reactions to the PEG component of vaccines [24][25][26], had undergone allergological consultations recommended by the Polish Allergological Society prior to being vaccinated [27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…The results of our study indicate that neither in the patients with a history of allergy/anaphylaxis nor in the non-allergic group, administration of the first dose effected sensitization to the vaccine components that would result in a higher rate of hypersensitivity reactions after the second dose. It needs to be emphasized, however, that the study patients with a history of allergy and/or anaphylaxis who demonstrated good vaccine tolerance constituted a group of individuals who had been qualified for vaccination following guidelines and recommendations prerequiring stratification and phenotyping of such patients [22,23]. Patients with a history of anaphylaxis to vaccines and injection drugs containing polyethylene glycol (PEG), as potentially susceptible to hypersensitivity reactions to the PEG component of vaccines [24][25][26], had undergone allergological consultations recommended by the Polish Allergological Society prior to being vaccinated [27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…The Pfizer-BioNTech SARS-CoV-2 vaccine is an mRNA vaccine that uses a lipid-based nanoparticle carrier system, stabilized by polyethylene glycol (PEG) 2000. Although evidence on the pathogenesis of severe immediate reactions to the SARS-CoV-2 vaccine is lacking, the PEG molecule has been proposed as a possible culprit for these reactions due to existing evidence of its ability to cause immunoglobulin E (IgE)-mediated anaphylaxis [ 4 5 6 ].…”
mentioning
confidence: 99%
“…The AstraZeneca COVID-19 vaccine has not been associated with a higher incidence of anaphylaxis, does not contain PEG 2000, and there is no evidence suggesting that hypersensitivity to the Pfizer-BioNTech vaccine would increase the risk of reaction to the AstraZeneca COVID-19 vaccine [ 5 ]. For the prementioned reasons, 2 of the 4 subjects were later inoculated with the AstraZeneca COVID-19 vaccine, with no immediate reactions ( Table 1 ).…”
mentioning
confidence: 99%
“…1) (European Space Agency (ESA) n.d.-a); European Space Agency (ESA) n.d.b). The impact of air pollution is not only a problem of western countries, but particularly affects developing countries: 193,000 European people died in 2012 from airborne particulate matter and 4000 preventable deaths each day in China with 1.6 million fatalities in 2016 (Wang et al 2012;Rohde and Muller 2015;Ortiz et al 2017). It is well-known that airborne particulate matter and radical species due to fossil fuel exhausts induce asthma, bronchitis, emphysema, lung and heart diseases, and respiratory allergies (Brauer 2010).…”
mentioning
confidence: 99%